DETERMINAN YANG MEMPENGARUHI PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Hismendi, Hismendi; Safaruddin, Safaruddin; Nasir, Muhammad; Abdullah, Ahmad Fauzan; Nadia, Siti (Jurnal Sosial Humaniora Sigli, 2023)
This research aims to determine the determinants that affect the profitability of Islamic Commercial Banks (BUS) in Indonesia. Profitability is measured by Return on Assets (ROA) as the dependent variable. Determinants that are expected to affect ROA consist of Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Operating Costs to Operating Income (BOPO) and Profit Sharing Financing (PBH) as independent variables. The data used is secondary data which is quarterly data for the period 2016 to 2020, obtained from the Financial Services Authority. The population of this study were all 14 BUS. Determination of the sample using purposive sampling and obtained as many as 5 BUS with an observation period of 20 quarters so that the number of observations is 100 observations. The data analysis technique uses panel data regression analysis. The results of this research indicate that NPF, FDR, BOPO and PBH simultaneously have a significant effect on BUS profitability in Indonesia. Furthermore, the partial test results found that BOPO and PBH had a significant negative effect and FDR had a significant positive effect on BUS profitability, while NPF was not significantKeywords : Profitability; Sharia Commercial Banks